Cryptic mediastinal masses causing airways obstruction. Issue 4 (April 1983) - Cooper, D K; Chrispin, A R; de Leval, M; Stark, J
Abstract : In 3 infants, severe airways obstruction was caused by mediastinal lesions which were not evident on the antero-posterior chest radiograph. Their presence was demonstrated by barium swallow examination. Each infant had thoracotomy carried out urgently. Duplication cysts (without associated cervicodorsal vertebral anomalies) were present in 2 patients and neuroblastoma in the third.